INTERNATIONALISATION OF THE PERFORMANCE OF A JSC LTD: CASE STUDY - Žaneta Kavaliauskienė; Urtė Tamulytė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
The article analyses how the internationalisation of the performance could help an enterprise to occupy a part of any foreign market. The subject of the study is the internationalisation of the performance of an enterprise. The study aims to choose the most attractive foreign market for the internationalisation of the performance a JSC Ltd. Considering the aim of the study, the following objectives were defined: to review the theoretical aspects of internationalisation processes; identify the modelling and filtering of the internationalisation of the performance; select the most reasonable foreign market for the integration of a JSC Ltd product. The research methods used in the study were the analysis and synthesis of theoretical sources, the analysis of filtering and the data of the performance of the enterprise, the collection of statistical data, and comparative analysis. The main outcomes of the research. The theoretical aspects of internationalisation processes have been examined, i.e. different approaches and forms of performance internationalisation are reviewed; the prevailing models of the internationalisation of the performance have been discussed, and the model of filtering internationalisation is presented; analysis of the internationalisation of the performance of an enterprise is provided. The results of the study obtained can be significant and practical to improve export of a JSC Ltd, as well as become a guideline for other small and medium-sized enterprises (SMEs) focusing on the internationalisation of their performance.